2020
DOI: 10.1051/itmconf/20203503017
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of a Computer Grading System for Teaching Mathematics at a University

Abstract: In the given work, the technology to create mathematical assignments with an auto-checking system in the MOODLE system to control education was considered. It is shown that due to using the STACK plugin, those assignments can be applied in all main sections of mathematical basics courses for engineering training: vector and matrix algebra, analytical geometry, mathematical analysis. The examples of interactive assignments for the development of mathematical thinking are listed. Two different methods of using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The three-level system avoids such effects from the beginning since students cannot copy solutions in level 2 but need to solve their individual examples. Tomilenko & Lazareva (2020), who use a comparable CAS, have shown that this has a positive effect on students' test scores.…”
Section: Solution Approachesmentioning
confidence: 98%
“…The three-level system avoids such effects from the beginning since students cannot copy solutions in level 2 but need to solve their individual examples. Tomilenko & Lazareva (2020), who use a comparable CAS, have shown that this has a positive effect on students' test scores.…”
Section: Solution Approachesmentioning
confidence: 98%
“…There are various forms of questions, such as multiple choice, true-false, matching, and even essay questions, that can be used as assessments (Chrisnawati et al, 2020). Another advantage is that the STACK plugin facility is available, which can be used for writing complete mathematics (Tomilenko & Lazareva, 2020). Complete math writing facilities are rarely found in quiz maker software or LMS.…”
Section: Introductionmentioning
confidence: 99%
“…Systems for Teaching and Assessment using Computer Algebra Kernel (STACK), is a computer-aided assessment plug-in for the Moodle Learner Management System that provides a high-order e-assessment in mathematics-related subjects. It is widely used in the deployment of formative and summative assessment tests in a number of contexts around the world [1]- [4].…”
Section: Introductionmentioning
confidence: 99%